(untitled) (Anclajes, 2024)
One of the driving forces behind Gregorio Prieto’s artistic production is a clear narcissistic impulse evident in the large number of self-portraits present both in his paintings and, above all, in the photographic series of his youth produced during his stay in Rome between 1928 and 1933. Through the screen of admiration for the classical world and the incorporation of avant-garde languages ―especially Surrealism― he constructed a sort of imagined biography in which the self-portrait functions as a form of affirmation of a self conscious of navigating in the realm of "difference". In contrast to some of his homosexual peers of his generation ―such as Lorca or Cernuda― there is no sign in his work of an anguished or unsettling vision of the homosexual experience; on the contrary, his work achieves a radically avant-garde (homo)sexual disinhibition.